Valuing vaccination - Bärnighausen, Till (National Academy of Sciences, 2014)
Vaccination has led to remarkable health gains over the last century. However, large coverage gaps remain, which will require significant financial resources and political will to address. In recent years, a compelling line of inquiry has established the economic benefits of health, at both the individual and aggregate levels. Most existing economic evaluations of particular health interventions fail to account for this new research, leading to potentially sizable undervaluation of those interventions. In line with this new research, we set forth a framework for conceptualizing the full benefits of vaccination, including avoided medical care costs, outcome-related productivity gains, behavior-related productivity gains, community health externalities, community economic externalities, and the value of risk reduction and pure health gains. We also review literature highlighting the magnitude of these sources of benefit for different vaccinations. Finally, we outline the steps that need to be taken to implement a broad-approach economic evaluation and discuss the implications of this work for research, policy, and resource allocation for vaccine development and delivery.